2005
DOI: 10.2224/sbp.2005.33.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Social Concerns and Willingness to Support Charities

Abstract: The market for charitable donations has its own functional systems. Well-known charities prevail by seeking donations and the competition can be intense. In this study we examine the factors affecting consumers' concerns about charitable donations and willingness to continue to support charities. Based on the results of this study, television and newspapers/magazines are major sources whence consumers gather charity information. The reputations of charities and the types of recipients are critical in gaining d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…With respect to attitudes and perceptions of control, charitable organisations should focus on highlighting the benefits of charitable giving, such as helping people in need, and the positive outcomes associated with charitable giving (see also Hsu, Liang, & Tien, 2005). Furthermore, charitable organisations would be advised to address the concerns that people might have in relation to charitable giving, such as whether the money donated reaches those in need, and potentially reconsidering the way in which people are approached for donations so as to avoid the perception that such organisations harass people for donations (see also Burgoyne et al, 2005; Polonsky et al, 2002).…”
mentioning
confidence: 99%
“…With respect to attitudes and perceptions of control, charitable organisations should focus on highlighting the benefits of charitable giving, such as helping people in need, and the positive outcomes associated with charitable giving (see also Hsu, Liang, & Tien, 2005). Furthermore, charitable organisations would be advised to address the concerns that people might have in relation to charitable giving, such as whether the money donated reaches those in need, and potentially reconsidering the way in which people are approached for donations so as to avoid the perception that such organisations harass people for donations (see also Burgoyne et al, 2005; Polonsky et al, 2002).…”
mentioning
confidence: 99%
“…Enthusiasm could come from psychographic and attitudinal profi les. Higher empathic dispositions and favorable perceptions of charities may lead to generosity and altruism in response to the misfortunes of the ( Hsu et al ., 2005 ). Effectiveness of monetary donations could be speedy without taking much energy as long as a person has hard cash and empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Factors shown to be signifi cant indicators of giving include general perceptions of charities ( Sargeant et al ., 2006 ), sense of social responsibility ( Bennett, 2003 ;Hsu et al ., 2005 ;Zhang et al ., 2007 ), familiarity with a charity ( Sargeant and Lee, 2002 ), and empathy ( Bennett, 1997 ;Sargeant, 1999 ;Schlegelmilch et al ., 1997 ). Individuals in societies that promote collectivism (i.e., Asian countries) are more likely to act on altruistic motives than those from societies based on individualism that value personal freedom and self-interest.…”
Section: Variable Selections In the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We were interested in examining whether these results are replicable in Eastern societies in which gender inequality prevails. In our literature review, we found that the majority of the studies related to donor behavior were conducted in Western nations and a few Southeast Asian countries like Taiwan (Hsu et al ., ; Lee and Chang, ) and China (Gan and Shan, ). Hence, we chose India, an Eastern nation that is a ‘fertile ground for the nonprofit sector’ (Sen, ) as our study setting.…”
Section: Literature Reviewmentioning
confidence: 99%